2011
DOI: 10.1088/0004-637x/735/2/102
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Simulations of Reconnection and Particle Acceleration: Three-Dimensional Effects

Abstract: The magnetic fields can change their topology through a process known as magnetic reconnection. This process in not only important for understanding the origin and evolution of the large-scale magnetic field, but is seen as a possibly efficient particle accelerator producing cosmic rays mainly through the first order Fermi process. In this work we study the properties of particle acceleration in reconnection zones and show that the velocity component parallel to the magnetic field of test particles inserted in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
229
5
17

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 155 publications
(275 citation statements)
references
References 32 publications
24
229
5
17
Order By: Relevance
“…Large scale magnetic reconnection events may be at the origin of large scale transient jets in microquasar systems (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014), for example via a magnetic field reversal accreted onto a magnetically arrested disk. Reconnection then occurs in the accretion disk coronae, near the black hole, where particle densities and magnetic fields are high.…”
Section: Objects and Orders Of Magnitudementioning
confidence: 99%
See 4 more Smart Citations
“…Large scale magnetic reconnection events may be at the origin of large scale transient jets in microquasar systems (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014), for example via a magnetic field reversal accreted onto a magnetically arrested disk. Reconnection then occurs in the accretion disk coronae, near the black hole, where particle densities and magnetic fields are high.…”
Section: Objects and Orders Of Magnitudementioning
confidence: 99%
“…It is a candidate for explaining (i) particle acceleration at pulsar wind termination shocks (Kirk & Skjaeraasen 2003;Pétri & Lyubarsky 2007;Sironi & Spitkovsky 2011a); (ii) the flat radio spectra from galactic nuclei and AGNs (Birk et al 2001) and from extragalactic jets (Romanova & Lovelace 1992); (iii) GeV flares from the Crab nebula (Bednarek & Idec 2011;Uzdensky et al 2011;Cerutti et al 2012aCerutti et al ,b, 2013; (iv) flares in active galactic nuclei (AGN) jets (Giannios et al 2009) or in gamma-ray bursts (Lyutikov 2006a;Lazar et al 2009); (v) the heating of AGN and microquasar coronae and the observed flares (Di Matteo 1998;Merloni & Fabian 2001;Goodman & Uzdensky 2008;Reis & Miller 2013;Romero et al 2014;Zdziarski et al 2014); (vi) the heating of the lobes of giant radio galaxies (Kronberg et al 2004); (vii) transient outflow production in microquasars and quasars (de Gouveia dal Pino & Lazarian 2005;de Gouveia Dal Pino et al 2010;Kowal et al 2011;Dexter et al 2014); (viii) gamma-ray burst outflows and non-thermal emissions (Drenkhahn & Spruit 2002;Giannios & Spruit 2007;McKinney & Uzdensky 2012); (ix) X-ray flashes (Drenkhahn & Spruit 2002); or (x) soft gamma-ray repeaters (Lyutikov 2006b;Uzdensky 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations